(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In the oil and gas industry, precise measurements of well parameters are key, provided by modern equipment such as logging tips. These devices not only transmit important data on the geological structure and composition of wells, but are also subject to significant mechanical loads and aggressive environments, which increases the problem of corrosion. An effective solution to this problem requires not only the selection of the right materials and coatings, but also the use of specialized processing technologies.